Computer simulation of defects and oxygen transport in yttria-stabilized zirconia - Devanathan, R.; Weber, W.; Singhal, S.; Gale, Julian (Elsevier, 2006)
We have used molecular dynamics simulations and energy minimization calculations to examine defect energetics and oxygen diffusion in yttria-stabilized zirconia (YSZ). Oxygen vacancies prefer to be second nearest neighbors to yttrium dopants. The oxygen diffusion coefficient shows a peak at 8 mol% yttria consistent with experimental findings. The activation energy for oxygen diffusion varies from 0.6 to 1.0 eV depending on the yttria content. The YZr' VO YZr' complex with a binding energy of -0.85 eV may play an important role in any conductivity degradation of YSZ.